Respuesta :
The answer is: 7/5 ; or write as: 1⅖ ; or write as 1.4 .
____________________________
Explanation:
________________
Given: f(x) = 5x − 10; Find f⁻¹(-3).
_____________________
→ Find: f ⁻¹(x) = 5x − 10 ;
__________________________
→ Write: f(x) = 5x − 10; as:
__________________________
→ y = 5x − 10 ;
________________
→ Replace the "x" with the "y", and the 'y" with the "x"; and Rewrite:
_________________
→ x = 5y − 10 ;
___________________
Now, rewrite the ABOVE equation in "slope-intercept form"; or "y = mx + b"; that is: with "y" as a "stand-alone" variable on the left-hand side;
_______________________
We have: x = 5y − 10 ;
____________________________
Subtract "x" ; and subtract "5y" ; from EACH side of the equation:
____________________________
→ x − x − 5y = 5y − 10 − x − 5y ;
→ -5y = -10 − x ; Multiply the ENTIRE EQUATION (both sides) by "-1" ;
→ -1* {-5y = -10 − x} ;
→ 5y = 10 + x ; ↔ 5y = x + 10 ;
→ Now, divide EACH side of the equation by "5" ;
__________________________________________
→ 5y / 5= (x + 10) /5 ;
→ y = x/5 + 10/5 ;
→ y = x/5 + 2 ; Now we can replace "y" with: f⁻¹(x) ;
→ f⁻¹(x) = x/5 + 2
________________
Now, to find: f⁻¹(-3) ; we plug "3" for "x" in this [inverse] function:
________________
→ f⁻¹(-3) = (-3)/5 + 2 = -⅗ + 2 = 7/5 ; or write as: 1⅖ ; or write as 1.4 .
________________________________________________________;
____________________________
Explanation:
________________
Given: f(x) = 5x − 10; Find f⁻¹(-3).
_____________________
→ Find: f ⁻¹(x) = 5x − 10 ;
__________________________
→ Write: f(x) = 5x − 10; as:
__________________________
→ y = 5x − 10 ;
________________
→ Replace the "x" with the "y", and the 'y" with the "x"; and Rewrite:
_________________
→ x = 5y − 10 ;
___________________
Now, rewrite the ABOVE equation in "slope-intercept form"; or "y = mx + b"; that is: with "y" as a "stand-alone" variable on the left-hand side;
_______________________
We have: x = 5y − 10 ;
____________________________
Subtract "x" ; and subtract "5y" ; from EACH side of the equation:
____________________________
→ x − x − 5y = 5y − 10 − x − 5y ;
→ -5y = -10 − x ; Multiply the ENTIRE EQUATION (both sides) by "-1" ;
→ -1* {-5y = -10 − x} ;
→ 5y = 10 + x ; ↔ 5y = x + 10 ;
→ Now, divide EACH side of the equation by "5" ;
__________________________________________
→ 5y / 5= (x + 10) /5 ;
→ y = x/5 + 10/5 ;
→ y = x/5 + 2 ; Now we can replace "y" with: f⁻¹(x) ;
→ f⁻¹(x) = x/5 + 2
________________
Now, to find: f⁻¹(-3) ; we plug "3" for "x" in this [inverse] function:
________________
→ f⁻¹(-3) = (-3)/5 + 2 = -⅗ + 2 = 7/5 ; or write as: 1⅖ ; or write as 1.4 .
________________________________________________________;